معاصرعرب ادبیات سیرت: کیف عاملھم کا منہج واسلوبContemporary ‘Arab Sīrah Literature: Style and Methodology of Kaifa ‘Āmiluhum by Muḥammad Ṣāliḥ al-Munjid (Al-Qamar, 2022)
The modern period, in terms of writings on the Prophet (PBUH), has been spectacularly productive. The classical Sīrah corpus in Arabian literary spheres during last two centuries, is generally an amalgam of prophetical traditions associated with ethical, social and political aspects. One core reason behind the plethora of the work, is to prevent the Islamic thought from the dominance of modern scientific thought emerged in the West, spread with the help of colonialism after the 19th century. As a result, the accumulation of writings on the conduct of Prophet (peace be on him) in the modern Arabian societies is variegated such as ‘AlāHāmiṣi’s Sīrah (1933) by Tāhā Ḥussein, Abqariyātu Muḥammad (The Genius of Mohammad) and Muḥammad Rasūl al-Ḥurriyat (Muhammad the Prophet of Freedom, 1962) by Abbas Mahmud el-‘Akkad (Egypt), Ḥayat-e-Muḥammad by Muḥammad Ḥuseyin Heykel, Sīret-e-Rasūl by Izzat Darwaza, Muḥammad the Big Revolutionist by Fethi Riḍwān and Istiṣrakiyyetū Muḥammad (Socialism of Muhammad) by Maḥmūd Shalbī. Among these splendid literary works, Kaifa ‘Āmiluhum by Muḥammad Ṣāliḥ al-Munjid belongs to the genre of social conduct of the Prophet (PBUH). This work comprises on a preface and six chapters. The preface belongs to preliminary sociology of Sīrah. In the chapters, the conduct of the Prophet (PBUH) about all walks of life has been discussed. The prime propose of this paper is to elaborate this magnum opus of Sīrah.
Keywords: Sīrah Writings; Methodology; Social conduct; Arabian literary Circles